Pemenuhan Hak Atas Informasi Konsumen Terhadap Produk Buah yang Mengandung Genetically Modified Organism di Yogyakarta - Aldila Surya Orienta (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The research in this study aims to determine the right to consumer information on fruit products containing genetically modified organisms in Yogyakarta. The problems raised are how to fulfill the right to consumer information on fruit products containing genetically modified organisms in Yogyakarta and how are the responsibilities of business actors for fruit products containing genetically modified organisms in Yogyakarta. This study uses an empirical legal research type. Research data were obtained by searching for primary data in the field by conducting interviews with informants and by document/library studies. This analysis was carried out using the provisions of Law Number 8 of 1999 concerning Consumer Protection and by looking at the actual situation in the field. The results of the study indicate that business actors still do not pay attention and there are still consumer rights that have not been fulfilled, one of which is the right to information for consumers. There are still consumers who are harmed by business actors due to the content of genetically modified organisms (GMO) in the fruit products traded and there are still many supermarkets and ordinary fruit shops that trade fruit products without labeling their products. Business actors also refuse to take responsibility for losses suffered by consumers on the grounds that the error came from consumers who did not seek information or ask in advance regarding the products being traded.